Performance Analysis of Mobile Anchor Assisted Circularized Localization Scheme in Wireless Sensor Networks - Mugunthan, S. R. (IRO Journal on Sustainable Wireless Systems, 2022)
A wireless sensor network is a large network with plenty of nodes for sensing and tracking network changes. High network mobility causes quality issues and may reduce delivery rate. Locating sensor node aids in accurate and loss-free data transmission to the destination. To locate the mobile nodes in a sensor network, a novel Mobile Anchor Assisted Circularized Localization Scheme has been proposed in this work. This proposed method uses a mobile assisted anchor node for determining the location of sensor nodes in a circularized manner. The position of the anchor node is determined by using control messages sent from the base station. Following the identification of the anchor node, the coordinates of nearby nodes are calculated using the circularized position and the Euclidian distance. This localization scheme aids in determining the precise position of the sensor node. Since the data is transmitted between known localized sensor nodes, the drop rate reduces while the delivery rate increases. The simulation result examines the performance of the proposed scheme using Quality of Service parameters such as throughput, drop rate and delivery rate. The proposed model achieves a higher delivery ratio and improves the overall network performance of the sensor network.
Keywords: Wireless sensor network; localization; delivery rate; anchor node; mobile node